Investigating the Impact of Entrepreneurial Infrastructure Deficit on Firm Growth - Baba Isah Usman; Zubairu Umaru Mustapha; Mohammed Dokochi; Jaafar Umar; Faiza Maitala (IJEBD (International Journal of Entrepreneurship and Business Development), 2019)
Small and medium enterprises (SMEs) in Nigeria are suffering from a deplorable condition of entrepreneurial infrastructure (EI) which is evidenced in the myriad of challenges bedevilling their growth and development. This study therefore aims to investigate the impact of EI deficit on firm growth, focusing on the growth of SMEs in Nigeria. This was done through a critical review of extant literature (peer reviewed journal articles) on EI which were obtained from reputable data bases and broken down into two basic components of infrastructure (physical and non-physical infrastructure). Empirical findings revealed that the availability of physical infrastructure (constant water supply and good road infrastructure) and the non-physical infrastructure (electricity, government policies/programmes, access to financial support services, incubation centers/platforms, business clusters and entrepreneurship training) improves productivity, profitability, sales, number of customers and consistent growth rate of SMEs. Findings of this study would be of help to entrepreneurs, policy makers and the academic community as it will add to the existing literature on how availability of EI impacts the growth of SMEs. The study recommends that government should use fiscal policies to address the economic challenges of SMEs and also invest in the provision of EI facilities to facilitate the growth and development of SMEs in Nigeria.